Transformasi SPBE Menuju Smart Governance Berbasis Kecerdasan Buatan Di Sidenreng Rappang - Sundari; Nonci, Nurjannah; Sinrang, Andi (LPPM STISIP IMAM BONJOL, 2024)
Digital transformation has become a key strategy to enhance the quality of governance and public service that is efficient, transparent, and accountable at the local level. This study aims to examine the implementation of the Electronic-Based Government System (SPBE) supported by Artificial Intelligence (AI) in Sidenreng Rappang Regency to realize smart governance. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed thematically with the aid of NVivo 12 Plus software. The findings indicate that AI-based SPBE implementation accelerates public service delivery, improves bureaucratic efficiency, enhances data-driven decision-making, and expands public information transparency. However, several challenges remain, including limited cross-agency system integration, digital infrastructure gaps in remote areas, insufficient digital human resource capacity, weak regulatory frameworks, and cybersecurity and data privacy risks. This study highlights the need to strengthen integrated digital governance, institutional capacity building, and cross-sectoral collaboration to ensure the sustainability of digital transformation toward smart, adaptive, and good governance-oriented public administration.